2014
DOI: 10.3855/jidc.4395
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin minimum inhibitory concentrations using different susceptibility methods in Staphylococcus aureus isolates

Abstract: This item has no abstract. Follow the links below to access the full text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…31 Vancomycin MICs generated by Etest® were consistently higher in the current study, according to other studies showing that Etest® MICs tend to be higher than BMD MICs. 16,32,33 The falsely elevated MIC of vancomycin may influence the clinicians to use another antimicrobial to replace vancomycin, and in another scenario, with the precise MIC value, vancomycin would be the first treatment choice. 34 Although new anti-staphylococcal antimicrobials have recently been developed, such as linezolid, vancomycin still remains the main therapeutic choice, mainly due to the low cost and the large number of clinical trials when compared to the new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…31 Vancomycin MICs generated by Etest® were consistently higher in the current study, according to other studies showing that Etest® MICs tend to be higher than BMD MICs. 16,32,33 The falsely elevated MIC of vancomycin may influence the clinicians to use another antimicrobial to replace vancomycin, and in another scenario, with the precise MIC value, vancomycin would be the first treatment choice. 34 Although new anti-staphylococcal antimicrobials have recently been developed, such as linezolid, vancomycin still remains the main therapeutic choice, mainly due to the low cost and the large number of clinical trials when compared to the new drugs.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that 124 S . aureus isolates from patient with bloodstream infection (BSI) from two tertiary hospitals in Rio de Janeiro, between 2008 and 2009, were susceptible to vancomycin [14]. However, VISA and hVISA infections are reported worldwide and have been associated with poor patient outcomes [7], [8], [15].…”
Section: Introductionmentioning
confidence: 99%